Peer involvement and cross-sector efforts in establishing integrated treatment of hepatitis C virus infection for people with substance use disorders: experiences from Norway - Ole Jørgen Lygren; Ronny Bjørnestad; Else-Marie Løberg; Martine Lepsøy Bonnier; Vibeke Bråthen Buljovcic; Kjell Arne Johansson; Lars T. Fadnes; for the INTRO-HCV Study Group (BMC, 2019)
Abstract Background For people with opioid dependence in Norway, chronic hepatitis C virus (HCV) infections contribute to high mortality and high morbidity. Around 50% of patients in medically assisted rehabilitation (MAR) have been shown to have HCV, and the current prevention and control efforts have been mostly unsuccessful. Thus, there is a need for new strategies for people-centred service delivery and innovative methods to improve health outcomes. Methods Over the last few years, the city of Bergen, Norway, has developed a cross-sector collaboration with substantial peer involvement in research and health provision related to substance use. User group representatives for people receiving MAR, addiction medicine health personnel, infectious disease specialists, policy makers in the municipality, low-threshold health care centres for people with substance use disorders in Bergen Municipality and researchers in the INTRO-HCV project have made concerted efforts in this regard. We will present here some of the strategies and steps we have taken. Results We have established an integrated HCV treatment scheme for people who inject drugs or who have opioid dependence. More than 800 persons have been tested for HCV within these frames, and more than 250 persons have been given treatment for HCV within the project. The integrated treatment of HCV is offered both in MAR outpatient clinics, municipal low-threshold healthcare centres, and local and regional prisons. The preliminary results indicate an increase in HCV treatment uptake among those receiving integrated treatment (96% initiating treatment compared to 75%). The user group organisation ProLAR Nett has established an outreach service to screen for HCV, increase awareness and reduce the proportion of people unknowingly living with HCV while informing and motivating people to receive treatment. Together with the other stake holders, peer user group, health care, research planning, concert events, and policy panels have been held. Conclusions Peer involvement seems to have increased testing rates for HCV and acknowledgment of its importance. This seems to have improved health care for people with opioid dependence in Bergen over the last few years, particularly relating to the treatment of HCV. These experiences might be helpful in the planning of integrated policies in other settings that seek to eliminate the HCV endemic.